Pengaruh webinar series “SIPEDE“ strategi intervensi gizi penyakit degeneratif terhadap pemahaman peserta: Studi pre-test dan post-test WEBINAR SERIES “SIPEDE“ STRATEGI INTERVENSI GIZI PENYAKIT DEGENERATIF TERHADAP PEMAHAMAN PESERTA: STUDI PRE-TEST DAN POST- TEST - Wityadarda, Carissa; Saputra, Mochamad Novian; Nurfadhilah, Andisa Alfani; Tirza Damar Ratri; Aditiyan, Nasya Salsabila; Ndopo, Fernando Diaz; Nurfadhilla, Nabilla Bilqi; Rahardianti, Syifha Nur Sallyima; Hardjanti, Maura; Parulian, Adi Anggoro; Victoria, Bernadette (ARGIPA (Arsip Gizi dan Pangan), 2025)
Lifestyle decisions, human behavior, and knowledge of dietary selections contribute to degenerative diseases. Indonesia has difficulty with nutrition literacy; this nutrition education needs to be more thorough. One way to do this is to use internet media, like webinars, to teach in a non-linear way. The objective of this study was to assess the impact of the “SIPEDE” webinar on participants’ comprehension of nutritional intervention techniques in the management of degenerative disease. A pre-experimental survey of 729 participants was administered prior to and after the intervention. We used pre-test and post-test questionnaires to collect data. These surveys asked about knowledge of degenerative disease, risk factors, and nutritional intervention options. A paired t-test was used to look at scores before and after the intervention. The results demonstrated a knowledge score enhancement of roughly 23,32% in the post-test, rising from 65,71 in the pre-test to 82,01 in the post-test (p<0,05). In other words, the webinar helped people learn more about nutrition and degenerative diseases, which makes it a good way to teach people about nutrition that can be used by many people in the community.